2020
DOI: 10.5812/aapm.107211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Critically Ill Patients Infected with COVID-19 in Rasoul Akram Hospital in Iran: A Single Center Study

Abstract: Background: Knowledge about clinical features of critically ill patients with COVID-19 still lacks adequate information up to now. Objectives: We aimed to describe and compare the epidemiological and clinical characteristics of critically ill patients with COVID-19 in Rasoul Akram Hospital. Methods: In this case series, 70 critically ill patients with COVID-19 admitted in ICU wards of Rasoul Akram Hospital, Tehran, Iran, from 29 February to 25 April 2020 were enrolled. Demographic and clinical characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Previous studies reported a wide range of mortality rates among critically ill patients admitted to ICU, from 16% to 38%, 62%, 67%, and 80% (12)(13)(14)(15)(22)(23)(24). In our study, overall outcomes were poor in severe patients who received ICU care, and the mortality rate (84.6%) was considerably higher than other studies.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies reported a wide range of mortality rates among critically ill patients admitted to ICU, from 16% to 38%, 62%, 67%, and 80% (12)(13)(14)(15)(22)(23)(24). In our study, overall outcomes were poor in severe patients who received ICU care, and the mortality rate (84.6%) was considerably higher than other studies.…”
Section: Discussioncontrasting
confidence: 60%
“…been conducted globally to discover a feasible, effective treatment. Unfortunately, critically ill and mechanically ventilated patients suffering COVID-19 show an overall higher mortality rate (10)(11)(12). Although vaccine development offers a glimmer of hope to end the current appalling pandemic, there is still a lack of definitive therapy, particularly for SARS-CoV-2-induced pneumonia (13).…”
Section: Contextmentioning
confidence: 99%
“…are at higher risk of death (11). Moreover, in the middle of a pandemic, health care systems face various challenges of which limited availability of resources is important because this limitation can impose a lot of stress on healthcare workers (12).…”
Section: Introductionmentioning
confidence: 99%
“…According to a review article, 14 - 32% of infected patients develop a critical illness, and 29-89% of patients with COVID-19 require mechanical ventilation support ( 10 ). Although critically ill patients with COVID-19 are not the majority of cases, they require more sophisticated care and are at higher risk of death ( 11 ). Moreover, in the middle of a pandemic, health care systems face various challenges of which limited availability of resources is important because this limitation can impose a lot of stress on healthcare workers ( 12 ).…”
Section: Introductionmentioning
confidence: 99%